1.3 kV Reverse-Blocking AlGaN/GaN MISHEMT With Ultralow Turn-On Voltage 0.25 V - Haiyong Wang (IEEE, 2021)
A reverse-blocking AlGaN/GaN metal-insulator-semiconductor high electron mobility transistor (RB-MISHEMT) is proposed and fabricated. Compared with the conventional MISHEMT with ohmic drain, the proposed device features a hybrid Schottky-ohmic drain with a low work function Tungsten (W), based on which the state-of-the-art ultralow turn-on voltage ( ${V} _{ on}$ ) of 0.25 V could be realized without degradation in on-state characteristics. In addition, the fabricated RB-MISHEMT exhibits the excellent reverse blocking voltage of −1332 V (at ${V} _{ GS}= 0$ V) and forward blocking voltage of 1315 V (at ${V} _{ GS} = -15$ V) with a specific on-resistance ( ${R} _{ on,sp}$ ) of 3.5 $\text{m}Ω $ cm2, leading in the highest power figure-of-merit (FOM) of > 494 MW/cm2. The good thermal stability could also be observed in fabricated RB-MISHEMT. The corresponding operation mechanism of RB-MISHEMT are also revealed by Silvaco ATLAS simulations. These results demonstrate the great potential in power electronics applications.